Protocol J - Silver staining of NOR regions [Pratical guide of protocols: methods of verification of the ploidy] - Basurco B.; Carrillo M.; Felip A.; Zanuy S.; Herráez M.P. (Advances in fish reproduction and their application to broodstock management: a pratical manual for sea bass, 2009)
The nucleolar organizer regions (NORs) contain the ribosomal genes (i.e., 18S and 28S rRNA). During metaphase they are within the 'stalks' (i.e., the secondary constrictions) of chromosomes, whereas during interphase they are located in the fibrillar components of the interphasic nucleolus where the rRNA-protein complex synthesized by active genes prior to interphase is localized. Many reports suggest that these proteins play an important role in its decondensation and/or in its transcription and thus, finally in the maturation of the rRNA. The proteins associated with NOR regions are known to be argyrophilic. Cytological tests have demonstrated that this strong affinity for silver nitrate only occurs for the decondensed state of NOR chromatin, either transcribing or ready for transcription. A method for the preparation of NOR regions is described in sea bass for counting interphasic nucleoli from newly hatched larvae. NORs are visualized by using silver staining to verify the ploidy condition in this species.